Sulfur-doped graphene as a catalyst support: Influences of carbon black and ruthenium nanoparticles on the hydrogen evolution reaction performance. (November 2015) - Shervedani, Reza Karimi; Amini, Akbar
Abstract: We develop an efficient electrocatalyst for hydrogen evolution reaction (HER) based on sulfur doped graphene nanosheets (S-GNs) synthesized with simple, cost effective and scalable method. The structure and morphological characteristics of the fabricated catalysts are investigated by field emission scanning electron microscopy, energy dispersive X-ray diffraction microanalysis, X-ray photoelectron spectroscopy, high resolution transmission electron microscopy and electrochemical methods such as voltammetry and impedance spectroscopy (EIS). Electrochemical results show that glassy carbon modified S-GNs heat-treated at 1000 °C (GCE-S-GNs-1000) benefit of a good activity toward HER compared to GNs. To improve the characteristics of S-GNs and prevent agglomeration of the layers, the GCE-S-GNs-1000-CB-Ru is fabricated by insertion of carbon black (CB) into S-GNs-1000, and further modification of GCE-S-GNs-1000-CB with ruthenium nanoparticles. The GCE-S-GNs-1000-CB-Ru demonstrated excellent performance for the HER, compared with its ancestors GCE-GNs-1000, GCE-GNs-1000-CB, GCE-S-GNs-1000, GCE-S-GNs-1000-CB as well as with traditional catalysts such as WS2 and MOS2 . Analysis of the results obtained by the EIS showed that the increase in the activity of the electrode was partially originated from increase in the double layer capacitance (surface roughness effect) and mostly from increase in the intrinsic activity (synergistic effect).